T-786C single nucleotide polymorphism of the endothelial nitric oxide synthase gene as a risk factor for endothelial dysfunction in polymyalgia rheumatica - Löffers, Christine; Heilig, Bernhard; Hecker, Markus (Clinical and experimental rheumatology, 2015)
OBJECTIVES: We investigated the association of the T-786C single nucleotide polymorphism (SNP) of the endothelial nitric oxide synthase gene (NOS3), which is characterised by reduced expression of the enzyme in response to shear stress or interleukin-10 stimulation and significantly associated with coronary heart disease or rheumatoid arthritis, with the occurrence of isolated polymyalgia rheumatica. - METHODS: A cohort of 78 patients who had presented at a rheumatological specialist practice in Heidelberg was tested for the T-786C SNP by means of restriction fragment length polymorphism analysis, and the result was compared with the data of a control cohort (n=2061) compiled from the genotyping of umbilical cord arteries from newborns. Patients were tested for an association with the genotype and their clinical characteristics obtained at the time of the initial presentation and during the first year of treatment. - RESULTS: The T-786C SNP of the NOS3 gene was significantly associated with isolated PMR (p=0.0009; OR 2.475). The C-allele frequency in patients with PMR was higher than in patients with rheumatoid arthritis, who also showed a significant association with the T-786C SNP (PMR 0.481 vs. 0.422 RA). A significant association with clinical features of the patients could not be detected. - CONCLUSIONS: The T-786C SNP of the NOS3 gene, which predisposes towards the development of endothelial dysfunction, is significantly associated with polymyalgia rheumatica manifesting itself without any clinically detectable vascular involvement.
Gesehen am 02.06.2020